MTHFR C677T gene polymorphism in patients with coronary heart disease and hypertension treated with enalapril and folic acid: implications for prognosis: MTHFR C677T gene polymorphism - Ma, Li; Zeng, Lanrui; Wang, Xiaowen (Cellular and Molecular Biology, 2024)
We aimed to investigate the effect of the methylenetetrahydrofolate reductase (MTHFR) C677T gene polymorphism on the prognosis of patients with coronary heart disease (CHD) and hypertension treated with enalapril and folic acid. A total of 540 CHD patients diagnosed by coronary angiography in our hospital were selected. According to whether there was folic acid intervention, they were divided into a folic acid group, a non-folic acid group and a control group. The genotypes of the MTHFR C677T locus were detected. Hcy concentration and the folate content were determined. In folic acid group, enalapril and folic acid tablets were used to reduce blood pressure, and clopidogrel or ticagrelor were selected according to CYP2C19 genotypes. In non-folic acid group, enalapril tablets were used, and clopidogrel or ticagrelor were selected based on CYP2C19 genotyping. Routine treatment without intervention was used in control group. Patients were prescribed standardized drug treatment and were followed up by an outpatient service or by telephone for 12 months after discharge. We found that the number and proportion of MTHFR C677T gene mutations in the folic acid group, non-folic acid group and control group were 150 (83.3%), 142 (78.9%) and 144 (80.0%), respectively. The recurrence rate of cardiovascular events in the folic acid and non-folic acid groups was significantly lower, and the degree of reduction in the recurrence rate of cardiovascular events in the folic acid and non-folic acid groups was significantly different. The concentrations of TG, TC, and LDL-C in folate and non-folic groups were lower, while HDL-C was higher than that in control group. To sum up, screening high-risk populations with genotypes has great significance in improving the clinical outcome of CHD patients with H-type hypertension. Folic acid supplementation improves the compliance rate of patients’ blood pressure levels and improves their clinical prognosis as well.